Street Discussion Spaces in Post-conflict Côte d'Ivoire: non-formal learning, dialogue and daily life - Marika Tsolaki (Universidade Federal do Rio Grande do Sul, 2018)
This paper frames the daily life of education outside of formal school, by considering two types of non-formal discussion spaces in Côte d'Ivoire. I argue that both traditional and modern learning were reinvented in the street in response to the Ivoirian political crisis through the proliferation of spaces called grins and agoras. At daily meetings, teenagers and adults gathered important information regarding the crisis and also learned how to be in a conflicted society, often through dialogic encounters between members of different generations, professions and experiences. In the post-conflict context, these spaces, and the dialogue within them, have evolved to meet the changing needs of participants, further highlighting the connection between learning in everyday life and the surrounding structures and systems.